Galaxy And Mass Assembly (GAMA): assimilation of KiDS into the GAMA database. Issue 3 (3rd June 2020) - Bellstedt, Sabine; Driver, Simon P; Robotham, Aaron S G; Davies, Luke J M; Bogue, Cameron R J; Cook, Robin H W; Hashemizadeh, Abdolhosein; Koushan, Soheil; Taylor, Edward N; Thorne, Jessica E; Turner, Ryan J; Wright, Angus H
ABSTRACT: The Galaxy And Mass Assembly Survey (GAMA) covers five fields with highly complete spectroscopic coverage (>95 per cent) to intermediate depths ( r < 19.8 or i < 19.0 mag), and collectively spans 250 deg 2 of equatorial or southern sky. Four of the GAMA fields (G09, G12, G15, and G23) reside in the European Southern Observatory (ESO) VST KiDS and ESO VISTA VIKING survey footprints, which combined with our GALEX, WISE, and Herschel data provide deep uniform imaging in the $FUV/NUV/u/g/r/i/Z/Y/J/H/K_s/W1/W2/W3/W4/P100/P160/S250/S350/S500$ bands. Following the release of KiDS DR4, we describe the process by which we ingest the KiDS data into GAMA (replacing the SDSS data previously used for G09, G12, and G15), and redefine our core optical and near-infrared (NIR) catalogues to provide a complete and homogeneous data set. The source extraction and analysis is based on the new ProFound image analysis package, providing matched-segment photometry across all bands. The data are classified into stars, galaxies, artefacts, and ambiguous objects, and objects are linked to the GAMA spectroscopic target catalogue. Additionally, a new technique is employed utilizing ProFound to extract photometry in the unresolved MIR–FIR regime. The catalogues including the full FUV–FIR photometry are described and will be fully available as part of GAMA DR4. They are intended for both standalone science, selection for targeted follow-up with 4MOST, as well as an accompaniment to the upcoming and ongoing radio arrays now studying the GAMA 23 h field.